Monoclonal antibodies against plasma protease inhibitors: II. Production and characterization of 25 monoclonal antibodies against human α1-antitrypsin. Correlation between antigenic structure and functional sites. Issue 2 (February 1984) - Hérion, P.; Siberdt, D.; Francotte, M.; Urbain, J.; Bollen, A.
Abstract : Twenty-five hybridomas secreting monoclonal antibodies against human α1 -antitrypsim have been produced by the cell-fusion techmque (Kóhler and Milstein, 1976). All antibodies are specific for α1 -antitrypsim and carry γ1 -antitrypsim heavy chains and κ light chains. Inhibition experiments showed that these monoclonal antibodies define three independent antigenic regions on the α1 -antitrypsim molecule; one of these domains appears to be involved in the interaction between α1 -antitrypsim and trypsin. In addition, one monoclonal antibody, AATY39, was used to develop an enzyme-linked immunosorbent assay capable of detecting low levels of α1 -antitrypsim in the range of 1 to 2 ng/ml.